Influence of Vine Vigor on Grape (Vitis vinifera L. Cv. Pinot Noir) Anthocyanins. 1. Anthocyanin Concentration and Composition in Fruit - Cortell, Jessica M; Halbleib, Michael; Gallagher, Andrew V; Righetti, Timothy L; Kennedy, James A (Journal of agricultural and food chemistry, 2007)
The relationships between grapevine (Vitis vinifera) vigor variation and resulting fruit anthocyanin accumulation and composition were investigated. The study was conducted in a commercial vineyard consisting of the same clone, rootstock, age, and vineyard management practices. The experimental design involved assigning vigor zones in two vineyard sites based upon differences in vine growth. Fruits and wines were analyzed by HPLC from designated vigor zones in 2003 and 2004. Average berry weight (grams), average dry skin weight (milligrams), degrees Brix, and pH were higher and titratable acidity (grams per liter) was lower in 2003 compared to 2004. In 2003, only the highest and lowest vigor zones had differences in berry weight, whereas there were no differences in 2004. In both years, high vigor zones had lower degrees Brix and higher titratable acidity (milligrams per liter). Accumulation of anthocyanins (milligrams per berry) was greater in 2003 compared to 2004. There was a trend for lower anthocyanin concentration (milligrams per berry) in high vigor zones in both years. In 2004 compared to 2003, there was a higher proportion of malvidin-3-O-glucoside and lower proportions of the other four anthocyanins (delphinidin-, cyanidin-, petunidin-, and peonidin-3-O-glucosides) found in Pinot Noir. In both years, site A had proportionally higher peonidin-3-O-glucoside and lower malvidin-3-O-glucoside than site B. Some of these differences may be related to the higher exposure and temperatures found in site B compared to site A and also in the low vigor zones. Keywords: Temperature; light exposure; yield; soluble solids; berry weight; skin weight; grape; anthocyanin; variation